Combining Diamond-Tip Dermabrasion Treatments and Topical Skincare in Participants with Dry, Hyperpigmented, Photodamaged or Acne-Prone/Oily Facial Skin: A Clinical Usage Study - Goberdhan LT; Schneider K; Makino ET; Mehta RC (Dove Medical Press, 2023)
Lisa T Goberdhan, Katie Schneider, Elizabeth T Makino, Rahul C Mehta SkinMedica; Allergan Aesthetics, an AbbVie Company, Irvine, CA, USACorrespondence: Katie Schneider, SkinMedica - Allergan Aesthetics, an AbbVie Company, 2525 Dupont Dr, Irvine, CA, 92612, USA, Tel +1 714 246-2573, Email katie.schneider@abbvie.comPurpose: An in-office diamond tip microdermabrasion device (DG) was designed to simultaneously exfoliate, extract, and infuse topical cosmetic serums into the skin to improve its appearance. Combining in-office procedures with take-home skincare may enhance treatment outcomes. This study aimed to assess the efficacy of a novel combination of DG treatments with a take-home cosmetic skincare regimen (DGR) to address facial dryness, hyperpigmentation, photodamage, or acne-prone/oily skin.Patients and Methods: In this 12-week, open-label, single-center study, participants were assigned to 1 of 4 groups according to skin presentation: dry, hyperpigmented, photodamaged, or acne-prone/oily. All participants received 6 bi-weekly DG treatments with tailored DGR topical products. During the DG treatment, the dry, hyperpigmented, photodamaged, and acne-prone/oily groups received hydrating, brightening, antioxidant, and pore-clarifying serums, respectively. Study endpoints included investigator grading, standardized photography, and participant questionnaires.Results: Sixteen participants aged 22 to 70 years with Fitzpatrick Skin Types I-V completed the study. Immediately after the first DG treatment, significant improvements in dryness, radiance, texture, photodamage, and fine lines were achieved (P< 0.01). At 72 hours, significant improvements were maintained in all these parameters except fine lines (P< 0.05). The DG and DGR combination provided significant long-term improvements at week 12 compared to baseline for dryness, radiance, texture, hyperpigmentation, photodamage, skin tone unevenness, and periocular/perioral fine lines (P< 0.05).Conclusion: The combination of DG and DGR showed significant immediate and long-term improvements in skin appearance. These results show that the DG and DGR combination is a well-tolerated and effective intervention to enhance different aspects of facial skin quality.Keywords: microdermabrasion, growth factors, antioxidants, photodamage, brightening, hydrating, DiamondGlow